Evolving engineering education: online vs. in-person capstone projects compared (EEE-OIPC) - Znidi, Faycal; Uddin, Md. Nizam; Morsy, Mohamed (Frontiers in Education, 2024)
This study compares online and face-to-face (F2F) instructional methods in Capstone Senior Design (CSD) projects across the disciplines of Electrical Engineering (EE) and Mechanical Engineering (ME). Through a comprehensive assessment involving project evaluations, advisor feedback, and self-peer reviews, it aims to gauge the efficacy of each approach in enhancing student success and learning outcomes. A key observation is the parity between online and F2F modalities in several metrics, yet F2F instruction distinctly advances teamwork and collaboration. Conversely, online environments show robust advisor evaluations, signifying effective mentoring despite hurdles in consistent team collaboration and project execution. Highlighting the imperative to blend online and traditional pedagogies, suggesting improved online strategies and a holistic curriculum to boost CSD students' learning experiences. These insights bear significance for ongoing and future STEM education research, stressing adaptable teaching techniques to better student experiences across varied settings. The outcomes yield important guidance for evolving STEM education research and practices, stressing the need for flexible teaching techniques to enrich learning in different educational environments. These findings are crucial for educators and institutions working to adapt their strategies to the changing landscape of online and F2F instruction in STEM areas.